Perilaku Pembungaan Galur-galur Tetua Padi Hibrida - Yuni Widyastuti; I. A. Rumanti; Satoto Satoto (Iptek Tanaman Pangan, 2012)
Rice (Oryza sativa L) is naturally a selfpollinated crop, although outcrossing rate of 0.5 to 6.8% had been observed in some genotipes. In hybrid rice breeding, outcrossing ability of parental lines is expected to increase seed set. The successful of hybrid rice seed production is affected by floral characteristics, synchronous of parental line flowering, and other morphological characters which affect pollen transfer from male parent (B or R line) to female parent (A line). Some rice agronomic characters such as number of productive tillers per hill, number of spikelets per panicle, plant height, narrow and short of flag leaf, also panicle exertion, could affect outcrossing rate. The floral characteristics of A line such as: stigma and stylus size, stigma exertion, stigma receptivity period, angle of floret, period of the spikelet opening, and panicle exerted above flag leaf, are also affecting the outcrossing rate. However, the flowering characteristic of male parent (B or R line) such as: anther size, filament length, number of pollen per anther, percentage of exerted anther and duration of spikelet opening, are also contributing to the rate of outcrossing. Study of heritability and genetic variability analysis revealed that all characters supporting outcrossing could be improved by breeding. The environmental factors that affect outcrossing in rice are temperature, relative humidity, light intensity, and wind speed.